Documentation as a tool for analysis and dissemination of the Cultural Heritage. The case of Franciscan Observance in Portugal, Italy and Spain - Genin, Soraya M.; Volzone, R.; Paio, A.; Brandão, Filipe J.S. (F-Atlas Conference Franciscan Observance Landscapes, 2023)
The importance of mendicant orders in shaping urban and rural landscapes is recognized worldwide. However, several sites are degraded and abandoned, instead of being valued and reused in a sustainable way. This is often related to their ignorance. This study aims to fill in this gap, through the documentation of the Franciscan Observance convents. It is presented the multidisciplinary methodology developed in three work packages coordinated by ISCTE, in the scope of the F-ATLAS project, for the documentation of the Italian, Portuguese and Spanish convents: census and case studies mapping (i), architectural and environmental analysis (ii), 3D digital prototyping (iii). The results obtained in the preliminary analysis reached 901 convents. 14 cases were selected for a detailed analysis in each country: 9 in Italy, 3 in Portugal, 2 in Spain. This represents the first step for the knowledge of these religious heritage sites and the starting point for their dissemination and valorization.